THE EFFECT OF MODIFIED COLLABORATIVE STRATEGIC READING AND VOCABULARY MASTERY ON THE READING COMPETENCY OF THE SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF MAHASARASWATI DENPASAR UNIVERSITY - Dharmayanti, Paramita; D.K, Tantra,; L., P., Artini, (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study focused oninvestigatingthe main effect of MCSR on second semester students? reading competency and the differential affect of MCSR between the students with good vocabulary mastery and with poor vocabulary mastery on students? reading competencyin EESP of Unmas Denpasar.The findings show thatthe students taught usingMCSRachieved better reading competency than those who were taught usingconventional teaching. Furthermore, there is an interactional effect between teaching strategies and vocabulary masteryon students? reading competency.The students with good vocabulary masteryimproved their reading competency when beingtaughtusingMCSR than usingconventional teaching.On the other hand, there is no difference in reading competency between the students who havepoor vocabulary mastery taughtwithMCSR and withconventional study.It can be concluded that this study provides an empirical evidence of the importance of the teaching strategy considering vocabulary mastery in English reading instructions. Keywords: MCSR, vocabulary mastery, reading competency